2022
DOI: 10.3390/jcm11133753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound-Guided Nerve Stimulation Targeting Peripheral Nerve Tissue on Pain and Function: A Scoping Review

Abstract: This paper assesses the effects of percutaneous electrical nerve stimulation (PENS) on pain- and function-related outcomes by means of a scoping review of studies with single cases, case-series, quasi-experimental, and randomized or non-randomized trial designs. We consulted the PubMed, MEDLINE and EMBASE databases. Data were extracted by two reviewers. The methodological quality of studies was assessed using the Physiotherapy Evidence Database (PEDro) scale for experimental studies and the Joanna Briggs Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These results should be considered under the premise that most conservative therapeutic approaches are based on traditional clinical reasoning that considers CTS just as a localized pathology associated with a lesion at the carpal tunnel and, therefore, most treatments are local, for example, splints, ultrasound, low‐level laser, TENS or corticoid injections. A scoping review found that application of PENS seems to be effective for different chronic pain conditions such as low back pain, rotator cuff repair, knee pain, elbow pain or ankle instability (García‐Collado et al, 2022). The current study increases evidence supporting the effects of PENS (applied to the median nerve) on a neuropathic pain condition such as CTS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results should be considered under the premise that most conservative therapeutic approaches are based on traditional clinical reasoning that considers CTS just as a localized pathology associated with a lesion at the carpal tunnel and, therefore, most treatments are local, for example, splints, ultrasound, low‐level laser, TENS or corticoid injections. A scoping review found that application of PENS seems to be effective for different chronic pain conditions such as low back pain, rotator cuff repair, knee pain, elbow pain or ankle instability (García‐Collado et al, 2022). The current study increases evidence supporting the effects of PENS (applied to the median nerve) on a neuropathic pain condition such as CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Although discussing the underlying mechanisms associated with PENS is beyond the scope of this study, some hypotheses can be proposed. First, it is possible that PENS could reduce nerve excitability (the median nerve) by altering nociceptive input and reducing neurogenic inflammation or ectopic discharge (García‐Collado et al, 2022). A recent meta‐analysis has concluded that PENS seems to be able to modulate altered pain processing by decreasing pain sensitivity and activating conditioning pain modulation, although further studies are needed to confirm this (Lagos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 However, since the use of US by physiotherapist got popular from 2006 after exploring the US utility for physiotherapists during the first Rehabilitative Ultrasound Imaging Symposium celebrated in Texas, 33 the inclusion of radiological education in physiotherapy undergraduate students is relatively novel compared with medical students. The use of radiological images as a complement for cross-sectional images may assist physiotherapy students in radiological identification of musculoskeletal structures while performing the clinical assessments (e.g., identifying the affected structures) or other invasive ultrasound-guided procedures placing the tip of the needle in the exact nerve branch or the exact tissular damage location (e.g., percutaneous electrical nerve stimulation 34 or percutaneous electrolysis 35 ). Yet, after a search in different databases [Medline® and PubMed (United States National Library of Medicine, National Institutes of Health, Bethesda, MD), Scopus® (Elsevier Inc., Amsterdam, The Netherlands), and Web of Science (Clarivate Analytics, Philadelphia, PA)] regarding the inclusion of cross-sectional and radiological images in undergraduate physiotherapy students, any study tested whether this methodology improves the students' anatomy and radiology understanding or assists the students in identifying high-risk structures during invasive procedures.…”
Section: Introductionmentioning
confidence: 99%